Impact of Organizational Commitment on Accounting Professionals’ Performance: Case of Accounting Firms - lassaad abdelmoula; sami boudabbous (STIE Malangkucecwara, 2021)
Purpose–This study examines the impact of organizational commitment(OC)on job performance. Two hundredforty professionals participated in this study. Design/methodology/approach–Our methodology has been applied toof 240 professional accountants who work in accounting offices in Tunisia. Findings–The results show that both affective and continuity dimensions have a positive and significant impact on performance, whereas the normative commitment has a positive but not significant effect. Originality/value–our knowledge, very little research has been conducted to investigate the accounting profession. our study aimed to fill this gap by studying the impact of OC on job performance of accounting professionals in the Tunisian context.